2000
DOI: 10.1093/auk/117.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Estimates of Peregrine Falcon Population Size in Northern Eurasia

Abstract: We used two different methods to estimate the density of nesting Peregrine Falcons (Falco peregrinus) across different parts of northern Eurasia. In the “territory-density” method, we extrapolated our density estimate of 406 km2 per territory (95% CI = 295 to 650 km2 per territory) in a high-density area, the Pyasina basin on the Taymyr Peninsula, to other similar areas across the range defined by published estimates. To estimate numbers in low-density areas, we used published data that suggested that Peregrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Deleterious Australia Olsen et al (1982) Decline Russia Quinn and Kokorev (2000) Gyrfalcon LC Exposed Norway Gjershaug, Kålås, Nygård, Herzke, and Folkestad (2008) Exposed Canada Poole and Bromley (1988) Exposed Iceland Ólafsdóttir, Petersen, Thordardottir, and Johannesson (1995) Exposed Europe Koskimies (2005) Black Falcon LC Exposed Australia Olsen et al (1993) Eurasian Merlin LC Thinning Norway Gjershaug et al (2008) Thinning Britain Newton and Haas (1988) Decline Britain Bibby and Nattrass (1986) Exposure Iran Behrooz et al (2009) American Merlin LC Exposure USA Becker and Sieg (1987) Deleterious Canada Fox and Donald (1980) Exposure-detection in or strong evidence for the bioaccumulation of pesticides.…”
Section: Iucn Organochloride Effect Region(s) Citation(s)mentioning
confidence: 99%
“…Deleterious Australia Olsen et al (1982) Decline Russia Quinn and Kokorev (2000) Gyrfalcon LC Exposed Norway Gjershaug, Kålås, Nygård, Herzke, and Folkestad (2008) Exposed Canada Poole and Bromley (1988) Exposed Iceland Ólafsdóttir, Petersen, Thordardottir, and Johannesson (1995) Exposed Europe Koskimies (2005) Black Falcon LC Exposed Australia Olsen et al (1993) Eurasian Merlin LC Thinning Norway Gjershaug et al (2008) Thinning Britain Newton and Haas (1988) Decline Britain Bibby and Nattrass (1986) Exposure Iran Behrooz et al (2009) American Merlin LC Exposure USA Becker and Sieg (1987) Deleterious Canada Fox and Donald (1980) Exposure-detection in or strong evidence for the bioaccumulation of pesticides.…”
Section: Iucn Organochloride Effect Region(s) Citation(s)mentioning
confidence: 99%
“…Similarly, several studies in different areas suggest that as much as 80% of the entire Red‐breasted Goose population associates with birds of prey (Dementiev & Gladkov 1952, Kretschmar & Leonovich 1967, Quinn & Kokorev 2002). Even though most of the Red‐breasted Goose's range has never been surveyed, the claim of an obligate association is backed up by the finding that trends in their numbers mirror the pesticide‐induced decline and eventual recovery of their main protective associate, the Peregrine Falcon, although trends for both species were based on limited data (Quinn & Kokorev 2000). Only a few studies on Hymenopteran–bird associations have been described in this paper but several older papers list countless records involving many different bird species (see papers cited in Moreau 1942, Durango 1949, Smith 1980) and it seems that it is here in the tropics that new obligatory nesting associations are most likely to be found.…”
Section: Population Processesmentioning
confidence: 99%
“…Earlier studies of bird communities have shown that densities of suitable-sized prey are lower near the breeding sites of raptors, but neither too large or small prey do not show such density responses or are more numerous near raptor nests than further away (Hunter et al 1989, Suhonen et al 1994, Norrdahl & Korpimäki 1998, Forsman et al 2001, Mönkkönen et al 2007. By killing nest robbing mesopredators, mainly Hooded Crows, Peregrines provide protection for species that are not important as their prey (Paine et al 1990, Norrdahl et al 1995, Quinn & Ueta 2008, Sergio et al 2008. Our data provide only partial support for the protection hypothesis, which states that preferred prey species should avoid the predator, in that preferred duck species avoided Peregrines (Quinn & Ueta 2008).…”
Section: Species Protection By Peregrinesmentioning
confidence: 99%